Pendampingan Transformasi Sistem Pembayaran Cash ke QRIS pada UMKM Baduy sebagai Upaya Modernisasi Transaksi Keuangan - Fitriah Fitriah; Yanto Nius Gulo (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2026)
The transformation of payment systems from cash to digital through the Quick Response Code Indonesian Standard (QRIS) is part of financial transaction modernization in Indonesia. This transformation has begun among Micro, Small, and Medium Enterprises (MSMEs) in the Baduy community, particularly in Baduy Luar, which has higher interaction with external communities. However, the adoption of digital payment systems has not been fully supported by adequate financial management capabilities. This community service activity aims to identify the transformation process of payment systems and describe the financial literacy conditions of Baduy MSMEs. The method used is a descriptive qualitative approach through in-depth interviews and field observations. The results show that some MSMEs have adopted QRIS through Bank BRI as an alternative payment method alongside cash and have utilized social media such as TikTok Live and Instagram for product marketing. The main sources of income include handicrafts, traditional clothing, accessories, and food products. However, financial management practices remain simple and lack systematic recording. This indicates improved financial inclusion but not yet accompanied by adequate financial behavior. Therefore, strengthening financial literacy is essential to support sustainable financial modernization in the Baduy community.